Environment-friendly fabric and preparation method thereof
By combining phosphorus-containing organic boron flame retardant with magnesium hydroxide and modification of nano zinc oxide and chitosan gel, the problem of poor flame retardant performance of polyester fabrics is solved, and the durability and antibacterial effect of flame retardant effect are achieved. Improved ultraviolet performance.
Patent Information
- Application Number
- CN202411334519.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
AI Technical Summary
Polyester fabrics have poor flame retardant performance, and existing flame retardant additives will be eluted after multiple washes, which cannot maintain the flame retardant effect.
The phosphorus-containing organic boron flame retardant is combined with magnesium hydroxide, combined with nano zinc oxide and chitosan gel modification to form a composite flame retardant and finishing solution, and improve the flame retardant of the fabric through chemical structure and physical modification. Antibacterial properties.
The flame retardant performance and stability of the fabric are significantly improved, and the flame retardant effect remains unchanged. Even after multiple washings, the flame retardant performance is still good, and the antibacterial and UV resistance is enhanced.
Smart Images

Figure BDA0005057903580000061 
Figure BDA0005057903580000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of fabric production, and in particular to an environmentally friendly fabric and a preparation method thereof. Background Art
[0002] Polyester is a polyester fiber, which is a green, environmentally friendly and renewable textile fabric. However, the flame retardant performance of polyester fabric is poor, and it can form molten drips when burning, causing the spread of flames and secondary damage.
[0003] In the current polyester processing and production process, flame retardant additives are mainly added during the finishing process of polyester fabrics, or a flame retardant coating is applied to the surface of polyester fabrics to improve the flame retardant effect of the fabrics. However, during the use of flame retardant fabrics, the flame retardant will be washed away after multiple washings, and the flame retardant effect of the fabrics cannot be maintained. Summary of the invention
[0004] In order to improve the flame retardant properties of polyester fabrics, the present application provides an environmentally friendly fabric and a preparation method thereof.
[0005] In the first aspect, the present application provides an environmentally friendly fabric, which adopts the following technical solution: An environmentally friendly fabric comprises the following raw materials in parts by weight: 80-100 parts of polyester, 10-20 parts of a composite flame retardant, and 5-15 parts of cellulose fibers; the composite flame retardant comprises the following raw materials in parts by weight: 15-25 parts of magnesium hydroxide, 3-5 parts of antimony trioxide, and 20-30 parts of a phosphorus-containing organic boron flame retardant.
[0006] By adopting the above technical scheme, phosphorus-containing organic boron flame retardant and magnesium hydroxide are compounded to improve the flame retardant properties of fabrics. Phosphorus-containing organic boron flame retardant has good flame retardant and smoke suppression properties, magnesium hydroxide has good flame retardant, smoke suppression and filling effects, and a small amount of antimony trioxide can play a catalytic role, forming a stable carbonization layer on the polymer surface to prevent the spread of flames, improve the flame retardant efficiency of the flame retardant, and reduce the use of excessive flame retardant additives. On the other hand, the phosphorus-containing organic boron flame retardant has a high similarity with the polyester matrix structure, which promotes good compatibility between the flame retardant and the polymer, and promotes the flame retardant and the polymer matrix to be firmly combined together, thereby improving the stability of the flame retardant effect of the fabric. By compounding organic flame retardants and inorganic flame retardants, the fabric has good flame retardant effect and flame retardant stability.
[0007] Preferably, the preparation method of the phosphorus-containing organic boron flame retardant comprises the following specific steps: mixing a boron-containing compound with glycerol, adding a catalyst, and then heating to 110-120° C. to react to form a boron-containing intermediate; Ethylene glycol is gradually added dropwise to the phosphorus-containing compound, and the gas is passed through sodium hydroxide for absorption, and a phosphorus-containing intermediate is obtained after the reaction; then a boron-containing intermediate is gradually added dropwise to the phosphorus-containing intermediate for reaction, and a phosphorus-containing organic boron flame retardant is obtained.
[0008] By adopting the above technical solution, the phosphorus-containing organic boron flame retardant generated by the reaction of phosphorus-containing and boron-containing compounds can maintain temperature at high temperatures, have high compatibility with the polymer matrix, and improve the stability of the flame retardant in the fabric. The phosphorus-containing organic boron flame retardant forms a stable carbonized layer during the combustion process through the chemical structure containing phosphorus and boron, prevents the spread of flames, and improves the flame retardant properties of the fabric. Phosphorus can form phosphate esters during the combustion process, and boron helps to form a carbonized layer. Under the combined effect, the flame retardant effect of the fabric can be significantly improved.
[0009] Preferably, the boron-containing compound is one of boric acid, methylboric acid, ethylboric acid, and p-ethylphenylboric acid, and the phosphorus-containing compound is one of trihydroxymethylphosphine oxide and phosphorus oxychloride.
[0010] Preferably, the mass ratio of the boron-containing compound to the phosphorus-containing intermediate is (0.5-0.8):1.
[0011] Preferably, the environmentally friendly fabric is treated with a finishing liquid, and the finishing liquid comprises the following raw materials in parts by weight: 5-10 parts of nano zinc oxide and 3-5 parts of polyethylene glycol.
[0012] By adopting the above technical scheme, nano zinc oxide has good antibacterial properties and ultraviolet absorption and scattering properties, can effectively inhibit the growth of microorganisms such as bacteria and fungi, reduce the odor on the fabric, and improve the antibacterial properties of the fabric. After the nano zinc oxide is used to finish the fabric, it can improve the ultraviolet protection performance of the fabric and reduce the damage of ultraviolet rays to the fabric and human skin. Polyethylene glycol can promote the uniform dispersion of nano zinc oxide on the surface of the fabric, and improve the dispersion and firmness of the finishing liquid on the surface of the fabric. At the same time, polyethylene glycol has good wettability and hygroscopicity, which can promote the fabric to absorb more finishing liquid, improve the finishing effect of the fabric, improve the feel and wearing comfort of the fabric, and make the fabric softer and smoother. At the same time, polyethylene glycol can improve the wrinkle resistance of the fabric, reduce the shrinkage of the fabric during washing and wearing, keep the fabric flat, and improve the appearance quality of the fabric.
[0013] Preferably, the nano zinc oxide is modified by an epoxy coupling agent.
[0014] By adopting the above technical solution, the epoxy coupling agent can enhance the bonding force between nano zinc oxide and fabric fibers, making the nano zinc oxide more firmly attached to the fabric, and improving the stability and durability of the fabric's anti-ultraviolet and antibacterial properties. At the same time, the epoxy coupling agent can improve the dispersibility of nano zinc oxide in the finishing liquid, making the nano zinc oxide more evenly dispersed on the fabric, and improving the uniformity of the fabric's anti-ultraviolet and antibacterial properties.
[0015] Preferably, the environmentally friendly fabric is pre-modified with chitosan gel.
[0016] By adopting the above technical solution, chitosan gel has good antibacterial properties and can further improve the antibacterial properties of fabrics. The modification of fabrics by chitosan gel can increase the hydrophilicity of fabrics. Chitosan gel has mucous membrane adsorption properties, which enhances the binding force between the finishing liquid and the fabric, promotes the firm deposition and embedding of nano zinc oxide in the fabric, and improves the stability of the fabric's anti-ultraviolet and antibacterial properties.
[0017] In a second aspect, the present application provides a method for preparing an environmentally friendly fabric, using the following technical solution: A method for preparing an environmentally friendly fabric comprises the following specific steps: mixing magnesium hydroxide, antimony trioxide and a phosphorus-containing organic boron flame retardant, stirring evenly to form a composite flame retardant, and then mixing polyester, the composite flame retardant and cellulose fibers, melt spinning, and weaving into a spinning yarn to obtain the environmentally friendly fabric.
[0018] By adopting the above technical solution, under the synergistic effect of various components, the prepared fabric has a strong flame retardant effect and flame retardant durability.
[0019] Preferably, nano zinc oxide and epoxy silane coupling agent are mixed in advance, heated to 50-60°C for reaction, and dried to obtain modified nano zinc oxide; chitosan gel is dissolved and mixed with water to form a chitosan treatment solution, and then the environmentally friendly fabric is immersed in the chitosan treatment solution and dried to obtain the modified environmentally friendly fabric; modified nano zinc oxide, water, and polyethylene glycol are mixed to obtain a finishing solution, and then the modified fabric is immersed in the finishing solution, dried, and baked to complete the finishing of the environmentally friendly fabric.
[0020] By adopting the above technical scheme, hydroxyl groups are loaded on the surface of the fabric modified by chitosan gel, and epoxy groups are loaded on the surface of the nano zinc oxide modified by epoxy silane coupling agent. The epoxy groups and hydroxyl groups react to promote the finishing liquid to be firmly embedded in the fabric, thereby improving the finishing effect of the fabric and improving the stability and durability of the fabric's anti-ultraviolet and antibacterial properties.
[0021] In summary, this application has the following beneficial effects: 1. Since the present application uses magnesium hydroxide, antimony trioxide and phosphorus-containing organic boron flame retardant to form a composite flame retardant, the principle of similar compatibility between phosphorus-containing organic boron flame retardant and polyester matrix is utilized to enable the flame retardant to be firmly combined in the fabric system, thereby improving the flame retardant effect and flame retardant stability in the fabric system.
[0022] 2. In this application, chitosan gel is used to modify the fabric, and epoxy silane coupling agent is used to modify nano zinc oxide, so that the hydroxyl groups loaded on the fabric react with the epoxy groups loaded on the nano zinc oxide, so that the finishing liquid is firmly embedded in the fabric, the finishing effect of the fabric is improved, and the fabric has better anti-ultraviolet and antibacterial properties. DETAILED DESCRIPTION
[0023] The present application is further described in detail below with reference to the embodiments.
[0024] All raw materials in the examples are commercially available.
[0025] Preparation example of phosphorus-containing organic boron flame retardant Preparation Example 1 The preparation method of the phosphorus-containing organic boron flame retardant comprises the following specific steps: S1: Mix the boron-containing compound with glycerol, add p-toluenesulfonic acid, the mass ratio of the boron-containing compound, glycerol and p-toluenesulfonic acid is 1:2:0.3, the boron-containing compound is boric acid, then heat to 115°C, keep warm in vacuum for 2 hours to form a boron-containing intermediate.
[0026] S2: gradually add ethylene glycol dropwise to the phosphorus-containing compound, the mass ratio of the phosphorus-containing compound to ethylene glycol is 1:2, the phosphorus-containing compound is phosphorus oxychloride, the released gas is passed into sodium hydroxide for absorption, and after reacting at room temperature for 2 hours, a phosphorus-containing intermediate is obtained.
[0027] S3: gradually adding the boron-containing intermediate to the phosphorus-containing intermediate for reaction, the mass ratio of the boron-containing compound to the phosphorus-containing intermediate is 0.7:1, the released gas is passed into sodium hydroxide for absorption, and after reacting for 2 hours at room temperature, a phosphorus-containing organic boron flame retardant is obtained.
[0028] Preparation Example 2 The difference between Preparation Example 2 and Preparation Example 1 is that the boron-containing compound in the phosphorus-containing organic boron flame retardant raw material is ethyl boric acid.
[0029] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that the phosphorus-containing compound in the phosphorus-containing organic boron flame retardant raw material is trihydroxymethylphosphine oxide. Example
[0030] Example 1 This embodiment provides an environmentally friendly fabric, including the following raw materials in parts by weight: 90kg polyester, 15kg composite flame retardant, and 10kg cellulose fiber. The composite flame retardant includes the following raw materials in parts by weight: 10kg magnesium hydroxide, 4kg antimony trioxide, and 25kg phosphorus-containing organic boron flame retardant. The phosphorus-containing organic boron flame retardant is derived from Preparation Example 1, the characteristic viscosity of polyester is 0.8mPa.s, the length of cellulose fiber is 2-3mm, the average particle size of magnesium hydroxide is 50-80nm, and the average particle size of antimony trioxide is 30-50nm.
[0031] The preparation method of the environmentally friendly fabric comprises the following specific steps: The magnesium hydroxide, antimony trioxide and phosphorus-containing organic boron flame retardant are mixed and stirred evenly to form a composite flame retardant, and then the polyester, the composite flame retardant and the cellulose fiber are mixed, melt-spun and spun into yarn to obtain an environmentally friendly fabric.
[0032] Example 2 The difference between Example 2 and Example 1 is that the amount of polyester used in the environmentally friendly fabric raw material is 80 kg, the amount of composite flame retardant used is 10 kg, and the amount of cellulose fiber used is 15 kg.
[0033] Example 3 The difference between Example 3 and Example 1 is that the amount of polyester used in the environmentally friendly fabric raw material is 100 kg, the amount of the composite flame retardant used is 20 kg, and the amount of cellulose fiber used is 15 kg.
[0034] Example 4 The difference between Example 4 and Example 1 is that the amount of magnesium hydroxide used in the composite flame retardant raw material is 15 kg, the amount of antimony trioxide used is 3 kg, and the amount of phosphorus-containing organic boron flame retardant used is 20 kg.
[0035] Example 5 The difference between Example 5 and Example 1 is that the amount of magnesium hydroxide used in the composite flame retardant raw material is 25 kg, the amount of antimony trioxide used is 5 kg, and the amount of phosphorus-containing organic boron flame retardant used is 30 kg.
[0036] Example 6 The difference between Example 6 and Example 1 is that the phosphorus-containing organic boron flame retardant in the composite flame retardant raw material comes from Preparation Example 2.
[0037] Example 7 The difference between Example 7 and Example 1 is that the phosphorus-containing organic boron flame retardant in the composite flame retardant raw material comes from Preparation Example 3.
[0038] Example 8 The difference between Example 8 and Example 1 is that the environmentally friendly fabric is treated with a finishing liquid, and the finishing liquid includes the following raw materials in parts by weight: 8 kg of nano zinc oxide and 4 kg of polyethylene glycol. The average particle size of the nano zinc oxide is 30-50 nm, and the polyethylene glycol is PEG200.
[0039] The preparation method of the environmentally friendly fabric comprises the following specific steps: S1: Mix magnesium hydroxide, antimony trioxide, and phosphorus-containing organic boron flame retardant, stir evenly to form a composite flame retardant, then mix polyester, the composite flame retardant, and cellulose fiber, melt-spin, and weave into yarn to obtain an environmentally friendly fabric.
[0040] S2: Mix nano zinc oxide, polyethylene glycol and water in a ratio of 1:30, stir evenly to form a finishing solution, and then put the environmentally friendly fabric into the finishing solution at a bath ratio of 1:30, dip and roll twice, then take out the fabric, dry it at 80°C for 2h, and bake it at 120°C for 3min, thus completing the finishing of the environmentally friendly fabric.
[0041] Example 9 The difference between Example 9 and Example 8 is that the amount of nano zinc oxide used in the finishing liquid raw materials is 5 kg, and the amount of polyethylene glycol used is 3 kg.
[0042] Example 10 The difference between Example 10 and Example 8 is that the amount of nano zinc oxide used in the finishing liquid raw material is 10 kg, and the amount of polyethylene glycol used is 5 kg.
[0043] Embodiment 11 The difference between Example 11 and Example 8 is that the nano zinc oxide in the finishing liquid raw material is modified by an epoxy coupling agent, and the epoxy coupling agent is KH560.
[0044] The preparation method of the environmentally friendly fabric comprises the following specific steps: S1: Mix magnesium hydroxide, antimony trioxide, and phosphorus-containing organic boron flame retardant, stir evenly to form a composite flame retardant, then mix polyester, the composite flame retardant, and cellulose fiber, melt-spin, and weave into yarn to obtain an environmentally friendly fabric.
[0045] S2: Mix the epoxy coupling agent with 60% ethanol aqueous solution in a mass ratio of 1:30 to form an epoxy coupling agent mixed solution, adjust the pH value of the epoxy coupling agent mixed solution to 5 with hydrogen chloride, heat to 55°C, stir and react for 1 hour, then add nano zinc oxide while keeping warm, the mass ratio of the epoxy coupling agent to the nano zinc oxide is 0.5:1, stir and react for 30 minutes, and obtain modified nano zinc oxide after drying.
[0046] S3: Mix modified nano zinc oxide, polyethylene glycol and water in a ratio of 1:30, stir evenly to form a finishing solution, and then put the environmentally friendly fabric into the finishing solution at a bath ratio of 1:30, dip and roll twice, then take out the fabric, dry it at 80°C for 2h, and bake it at 120°C for 3min, thus completing the finishing of the environmentally friendly fabric.
[0047] Example 12 The difference between Example 12 and Example 11 is that the environmentally friendly fabric is modified with chitosan gel in advance.
[0048] The preparation method of the environmentally friendly fabric comprises the following specific steps: S1: Mix magnesium hydroxide, antimony trioxide, and phosphorus-containing organic boron flame retardant, stir evenly to form a composite flame retardant, then mix polyester, composite flame retardant, and cellulose fiber, melt-spin, and weave into yarn to obtain environmentally friendly fabrics; dissolve chitosan in acetic acid, and then mix the dissolved chitosan with water, the mass ratio of chitosan to water is 1:40, to form a chitosan treatment solution, and then immerse the environmentally friendly fabric in the chitosan treatment solution, react while stirring for 60 minutes, then take out the fabric, perform two immersions and two rollings, and dry to obtain the modified environmentally friendly fabric.
[0049] S2: Mix the epoxy coupling agent with 60% ethanol aqueous solution in a mass ratio of 1:30 to form an epoxy coupling agent mixed solution, adjust the pH value of the epoxy coupling agent mixed solution to 5 with hydrogen chloride, heat to 55°C, stir and react for 1 hour, then add nano zinc oxide while keeping warm, the mass ratio of the epoxy coupling agent to the nano zinc oxide is 0.5:1, stir and react for 30 minutes, and obtain modified nano zinc oxide after drying.
[0050] S3: Mix modified nano zinc oxide, polyethylene glycol and water in a ratio of 1:30, stir evenly to form a finishing solution, and then put the modified environmentally friendly fabric into the finishing solution at a bath ratio of 1:30, dip and roll twice, then take out the fabric, dry it at 80°C for 2h, and bake it at 120°C for 3min, thus completing the finishing of the environmentally friendly fabric.
[0051] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no phosphorus-containing organic boron flame retardant is used in the environmentally friendly fabric raw material.
[0052] Performance testing According to the environmentally friendly fabrics provided in Examples 1-12 of the present application and Comparative Example 1, the following performance tests were performed, and the specific test results are shown in Table 1.
[0053] Detection Methods 1. Flame retardant properties According to GB / T 5454-1997 "Textile Combustion Performance Test - Oxygen Index Method", the environmentally friendly fabrics were tested for the limit oxygen index and the oxygen index after 100 soap washes.
[0054] 2. Anti-ultraviolet performance Referring to the standard of GB / T 18830-2002 "Evaluation of UV protection performance of textiles", the UV protection index and UV transmittance T (UVA) of the environmentally friendly fabric prepared in this application were tested. AV , and the UV protection index after 100 soap washes.
[0055] Table 1: Performance test results data table It can be seen from the performance test results that the environmentally friendly fabric prepared by the present application has good flame retardant effect and durability, and can still maintain a high oxygen index after several washings. By comparing Comparative Example 1 with Example 1, it can be seen that Comparative Example 1 does not use phosphorus-containing organic boron flame retardant, and although the fabric still has good flame retardant properties, the flame retardant effect of the fabric has been significantly reduced after washing, which further illustrates that the present application uses phosphorus-containing organic boron flame retardant compounded with magnesium hydroxide and antimony trioxide, and utilizes the characteristics of phosphorus-containing organic boron flame retardant and polyester matrix structure similarity and compatibility, thereby improving the compatibility and bonding between the flame retardant and the polymer, and thus enhancing the flame retardant effect stability of the fabric.
[0056] By comparing Examples 8-10 with Example 1, it can be seen that by using nano zinc oxide and polyethylene glycol to finish the environmentally friendly fabric, it can be seen from the performance test results that the prepared environmentally friendly fabric has a higher UV protection index and a lower UV transmittance, indicating that nano zinc oxide has been embedded in the environmentally friendly fabric. At the same time, the flame retardant effect of the fabric is further improved, indicating that polyethylene glycol can form a film and disperse on the surface of the fabric, thereby reducing the shedding of the flame retardant and improving the flame retardant effect and flame retardant durability of the fabric.
[0057] By comparing Examples 11-12 with Example 8, it can be seen that the nano zinc oxide is modified in Example 11, and the environmentally friendly fabric is also modified in Example 12. From the performance test results, it can be seen that after several washes, the fabric still has a high UV protection index and a low UV transmittance, which further illustrates that the hydroxyl groups loaded on the fabric react with the epoxy groups loaded on the nano zinc oxide, and the binding force of the finishing liquid on the fabric is stronger, thereby improving the finishing effect and UV resistance durability of the fabric.
[0058] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An environmentally friendly fabric, characterized in that: The composite flame retardant comprises the following raw materials in parts by weight: 80-100 parts of polyester, 10-20 parts of composite flame retardant and 5-15 parts of cellulose fiber; the composite flame retardant comprises the following raw materials in parts by weight: 15-25 parts of magnesium hydroxide, 3-5 parts of antimony trioxide and 20-30 parts of phosphorus-containing organic boron flame retardant.
2. The environmentally friendly fabric according to claim 1, characterized in that: The preparation method of the phosphorus-containing organic boron flame retardant comprises the following specific steps: mixing a boron-containing compound with glycerol, adding a catalyst, and then heating to 110-120° C. for reaction to form a boron-containing intermediate; Ethylene glycol is gradually added dropwise to the phosphorus-containing compound, and the gas is passed through sodium hydroxide for absorption, and a phosphorus-containing intermediate is obtained after the reaction; then a boron-containing intermediate is gradually added dropwise to the phosphorus-containing intermediate for reaction, and a phosphorus-containing organic boron flame retardant is obtained.
3. The environmentally friendly fabric according to claim 2, characterized in that: The boron-containing compound is one of boric acid, methylboric acid, ethylboric acid and p-ethylphenylboric acid, and the phosphorus-containing compound is one of trihydroxymethylphosphine oxide and phosphorus oxychloride.
4. The environmentally friendly fabric according to claim 2, characterized in that: The mass ratio of the boron-containing compound to the phosphorus-containing intermediate is (0.5-0.8):
1.
5. The environmentally friendly fabric according to claim 1, characterized in that: The environmentally friendly fabric is treated with a finishing liquid, and the finishing liquid comprises the following raw materials in parts by weight: 5-10 parts of nano zinc oxide and 3-5 parts of polyethylene glycol.
6. The environmentally friendly fabric according to claim 5, characterized in that: The nano zinc oxide is modified by an epoxy coupling agent.
7. The environmentally friendly fabric according to claim 5, characterized in that: The environmentally friendly fabric is modified by chitosan gel in advance.
8. A method for preparing the environmentally friendly fabric according to any one of claims 1 to 7, characterized in that: The method comprises the following specific steps: mixing magnesium hydroxide, antimony trioxide and phosphorus-containing organic boron flame retardant, stirring evenly to form a composite flame retardant, and then mixing polyester, the composite flame retardant and cellulose fiber, melt spinning and weaving into yarn to obtain environmentally friendly fabric.
9. The method for preparing the environmentally friendly fabric according to claim 8, characterized in that: Nano zinc oxide and epoxy silane coupling agent are mixed in advance, heated to 50-60°C for reaction, and dried to obtain modified nano zinc oxide; chitosan gel is dissolved and mixed with water to form a chitosan treatment solution, and then the environmentally friendly fabric is immersed in the chitosan treatment solution and dried to obtain modified environmentally friendly fabric; modified nano zinc oxide, water, and polyethylene glycol are mixed to obtain a finishing solution, and then the modified fabric is immersed in the finishing solution, dried, and baked to complete the finishing of the environmentally friendly fabric.
